MENGASAH KREATIVITAS ANAK-ANAK TAMAN KANAK-KANANDAN SEKOLAH DASAR DI DUSUN BANDUNG DAN DUSUN 194 SONGBANYU 1,KECAMATAN GIRI SUBO, GUNUNG KIDUL,DAERAH ISTIMEWA YOGYAKARTAMELALUI BELAJAR MENGGAMBAR DAN MEWARNAI - Muntoha Muntoha (Asian Journal of Innovation and Entrepreneurship, 2015)
Creativity is the ability to imagine, interpret, and present ideas and businesses thathave creativity to new combinations of previously existing elements in order to obtain anincrease in the quality of a person in his development. Creativity is an important key foreveryone to deal with changes in their lives and life itself. There is no difference forchildren. Unfortunately, children at Dusun Bandung and Dusun Songbanyu 1, KecamatanGiri Subo, Gunung Kidul, Daerah Istimewa Yogyakarta in their daily life just filled withplaying and readingAl-Qur’an. Although helpful, monotonous activity will not help thedevelopment of their creativity. Therefore, author took the initiative to organize a funactivity and inovastif to hone the creativity of children at those two hamlets.. The activitywas studied drawing and coloring.